(untitled) (Research, Society and Development, 2022)
However the great richness of plant species present in the Amazonia, in there still much to be better used of this heritage, such as the great potential of its landscapes. So, the Universidade Federal Rural da Amazônia (UFRA) in Belém, Pará, Brazil (1°27’22"S 48°26’14"W), is characterized in this study through a wide and detailed work of scientific research, over the ornamental plants that compunds the landscaping from the institution. The aim of this study was identify and map the plant species used in the landscaping from the UFRA’s Campus in Belém. Thus, a floristic survey was realize through collection and identification techniques of plant specimens, as well as data analysis, in the end, 187 species, 156 genera, distributed in 57 families were identified. The five families with the highest number of species are: Fabaceae, Asparagaceae, Arecaceae, Apocynaceae and Araceae. Rubber trees (Hevea spp.) and maxarimbé (Cenostigma tocantinum Ducke) are the tree species that occur in the area with the highest number of individuals, both being native from Brazil. However, exotic species (53%) predominated over native ones (47%). The results indicate the need to value the use of native species in the institution’s landscaping. As well as, the database presented here is useful for carrying out other studies.